Optimizing parental care in preventing bullying behavior in children in Wonokromo Surabaya Village - Nur Hidaayah; Syidatul Budury; Nunik Purwanti; Mery Susantri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Parents who do not teach or model positive behavior to their children are at risk of forming children who have a tendency to bully other children. In addition, if parents do not consistently give consequences to children when they make mistakes or break the rules, it will increase the possibility of children being at risk of bullying. The community service aims to increase parents' understanding and attitude towards parenting in preventing bullying in children. Educational activities on proper parenting in preventing bullying in children are carried out offline with hands-on practice, discussion, and questions and answers. Media PowerPoints, leaflets, and daily notebooks have been given to 20 parents in the Wonokromo Surabaya Village area. Initial and final evaluation using questionnaires distributed before and after education to determine the level of parental knowledge of bullying. Data were processed by frequency distribution. There was an increase in understanding shown by almost all participants showing positive parenting attitudes in preventing bullying behavior in children. Education is only carried out once a time, so the change in parents' attitudes is not entirely positive. Therefore, there is a need for follow-up with in-depth evaluations regarding child care that the team continues to carry out.